Assessing the impact of stone quarrying on the landscape, crop and grazing land degradation in Loma Bosa district, Dawuro zone, southern Ethiopia - Balcha, Damte; Oyda, Semayat (International Journal of Scientific Research in Civil Engineering, 2021)
A quarry is a type of open-pit mine from which rock or minerals are extracted. The end product materials from the quarries include marble, gravel, granite, dimension stone and limestone which are regarded as inevitable in modern civil engineering and construction works. The main objective of this research was analysis of the impact of quarry on land escape, crop land, crop yield and grazing land in local resident. The study area is located in southern region, Dawro zone, Loma district, (Ethiopia), In addition, questioners were prepared both close and open ended type to deal the impact of quarry on resident; around  the quarry site , with in the quarry and to analyses the impact and its beneficial use for generation of income from quarry. The questioner survey analyzed through frequency percentage and shows the impact becomes maximum during its operation. The data were collected from different target groups in order to get the actual information about impacts of quarrying.  We have analyzed the data by using tables and percentage interpretation; quarrying has substantial impacts on the socio-economic activities and on the physical environment (during land clearing and excavation activities).  It also substantially reduces crop and forage land which would, in turn, affects economic, social and ecological.  Generally the quarry operation leads to destruction and degradation of the land, air pollution, accident, land escape change, and crop land change. we have seen the socio economic impact, impact on the land escape, impact on the crop yield and the environmental impacts of quarrying.
Keywords: Soil And Water; Soil Productivity; Soil Quality; Sustainability; Management